A cleaner route of biodiesel production from waste frying oil using novel potassium tin oxide catalyst: A smart liquid-waste management. (November 2021) - Roy, Tania; Ágarwal, Avinash Kumar; Sharma, Yogesh Chandra
Graphical abstract: Highlights: Valorization of waste frying oil into biodiesel. A novel potassium tin oxide (KSO 800) catalyst was used for biodiesel production. The catalyst showed no leaching of K-species upto 5th cycle. 98% FAME conversion and 96% yield was achieved within 35 min. This catalytic process followed a cleaner and greener route. Abstract: The valorization of waste frying oil (WFO) to biodiesel has been carried out via solid base catalyzed transesterification reaction. A novel potassium tin oxide (KSO) catalyst was synthesized via polymer precursor auto combustion method. The catalyst showed the best physicochemical properties when it was calcined at 800 °C. Using KSO 800 catalyst, the highest FAME conversion (99.5%) of WFO found at moderated reaction condition within very short time (35 min); moreover, no leaching of K-species was observed in reusability test upto 5 th cycle. Kinetics proved that the above catalytic reaction followed pseudo-first-order kinetics and the rate of the reaction was doubled with increasing 10 °C reaction temperature. The reaction activation energy, enthalpy of activation, entropy of activation, and Gibb's free energy of activation of the reaction were found to be 66.52 kJ/mol, 62.95 kJ/mol, −74.07 J/mol/K and 88 kJ/mol respectively. Evaluation of the green parameters revealed that KSO 800 catalyzed transesterification process approached a cleaner route with excellent efficacy in terms of turnover frequency and yield. KSO 800 helped to produce high quality biodiesel from WFO adopting faster and greener reaction pathway. Thus, KSO 800 was considered as a potential and green catalyst for transforming waste oil into biofuel.